Analyzing Coastal Vulnerability Using Analytic Hierarchy Process and Best-Worst Method: A Case Study of the Marmara Gulf Region - Arda, Tumay; Bayrak, Onur Can; Uzar, Melis (SPRINGER HEIDELBERG, 2025)
Coastal regions, integral to human economic and social frameworks, face increasing threats from disasters and climate change. This situation has made it necessary and a priority to study these areas at an international level. To be able to take precautions, protect, and manage coastal areas, it is essential to identify their coastal vulnerability. In this study, a coastal vulnerability analysis was conducted using best-worst method (BWM) in the Marmara Gulf Region, T & uuml;rkiye. Moreover, comparison was made with the analytic hierarchy process (AHP) method in the subject of assessment of coastal vulnerability. According to the vulnerability map obtained with AHP, 17% of the region was determined to have a moderate vulnerability risk, 54% had a high risk, and 29% had a very high risk. On the other hand, the analysis results in BWM calculated the vulnerability percentages as follows: 18% moderate vulnerability, 57% high vulnerability, and 25% very high vulnerability. Visual and statistical comparisons revealed that the BWM method provides more consistent results and involves fewer pairwise comparisons than the AHP method. Thus, it offers ease of use and convenience to decision maker while maintaining relatively same level of weights for criteria. This study aims to lay the foundation for a dynamic system designed to assess coastal vulnerability, emphasizing usability for policymakers in decision-making and flexibility across various scenarios. Particularly, the adoption of the BWM provides notable benefits due to its direct approach and ability to yield more uniform and dependable evaluations, thereby efficiently addressing intricate decision-making challenges.
Keywords: Coastal vulnerability; Climate change; Analytic hierarchy process; Best-worst method; Geographic information system; SEA-LEVEL RISE; SOCIAL VULNERABILITY; INDEX; COMMUNITIES; AHP; Science & Technology - Other Topics